Optical spectroscopy of In-based fluoride glasses doped with Er3+ and Yb3+ ions - Ribeiro, CTM; Zanatta, A. R.; Sartori, J.; Nunes, LAO; Messaddeq, Y. (Soc Brasileira Quimica, 1998)
Optical spectroscopy in the 400-1700nm wavelength range was performed on rare earth doped heavy metal fluoride (HMF) glasses. In the present work In-based fluoride glasses with a fixed 2 mol % YbF3 concentration and an ErF3 content ranging from 0 to 8 mol % were investigated, According to the experimental spectroscopic data a dependence in the absorption coefficient, the photoluminescence intensity and in the radiative lifetime could be verified as a function of the ErF3 content. In addition, at liquid nitrogen temperature, light emission corresponding to indirect transitions in the infrared energy range could be easily observed as a consequence of the low phonon frequency characteristic of this class of fluoride glasses. For all the studied compositions, strong upconversion to the green and red. light was observed by pumping these Er3+- and Yb3+-doped HMF glasses with 790 and 980nm photon sources.
Keywords: optical spectroscopy; rare earth doped glasses; upconversion